Pension Funds and the Politics of Ownership in Britain, c. 1970–86. (23rd April 2018) - Davies, Aled
Abstract: The growth of occupational pensions in the post-war era transformed the pattern of capital ownership in Britain, as workers' collective retirement savings purchased a substantial share of the national economy. This article examines the response of the Labour and Conservative parties to this significant material change, and considers how it shaped their respective politics of ownership at the end of the post-war settlement. It demonstrates that Labour and the trade union movement recognized occupational pension funds as a new form of social ownership but had to reconcile their desire to give pension scheme-members direct control over their investments with a broader belief that the funds needed be used for a state-coordinated revitalization of the industrial economy. Meanwhile, the Conservative Party's initial enthusiasm for occupational pensions, which it championed for helping to create a 'property-owning democracy', was challenged by a radical neoliberal critique in the early 1980s that sought to dismantle pension funds and to individualize investment. The findings in the article assert the need for historians to situate the politics of the tumultuous 1970s and 1980s in the context of the substantial economic and social changes that had taken place during the post-war decades. These changes often created opportunities to formulate new policies and political agendas, but they also served to highlight deeper tensions within the ideologies of the main political parties.